Application of satellite remote sensing in forest change detection and its environmental impacts in district Abbottabad, Pakistan - Zaib un Nisa; Mir, Kamran; Fatimah, Hina; Batool, Syeda Maleeha; Sanaullah; Atif, Salman; Awan, Muhammad Arshad (Journal of Pure and Applied Agriculture, 2023)
Decline of natural resources poses significant impact on society directly or indirectly. Change in the forest area can affect the climate and economy of a society. This study highlights the effect of forest increase on surface temperature conditions of Abbottabad. The scope of this study covers the forest change detection of district Abbottabad (Pakistan) using Landsat 5 TM data over the period of 9 years (2000 and 2009) and its subsequent impact on land surface temperature. A Python (Programming) based tool was developed to automate this change detection procedure. Results indicate that almost 1% of the forest area (from 13% to 12% of total land area) has undergone deforestation in 9 years, however vegetation has increased 36% in 2009, 51.6% decline in the past 2000 vegetation cover which is an indication of substantial deforestation. A significant change in land surface temperature of Abbottabad was observed by 90 fall in maximum and -100 fall in minimum temperature, that deciphers cooler conditions. Study concludes that change in climate is not solely dependent on deforestation but also GIS automated assessment of forest change detection is possible in GIS via python tool. This tool can speed up the process of forest change detection and assessment in Pakistan.